2020
DOI: 10.18332/tid/122759
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive characteristics of hospitalized adult smokers and never-smokers with COVID-19

Abstract: A meta-analysis done by Guo 1 that was published in Tobacco Induced Diseases, reported a pooled odds ratio of 2.20, concluding that active smoking is significantly associated with the risk of severe COVID-19. Another current meta-analysis reported greater odds of COVID-19 progression among smokers compared to never smokers 2. Most of the studies in these meta-analyses were from China and focused only on cigarette smoking 1,2. Here, we describe characteristics of tobacco use among 193 confirmed COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study in Iran showed that among 193 confirmed COVID-19 patients, more than half of cigarette smokers and 40% of waterpipe smokers reported their COVID-19 symptoms as severe compared to 22% of never-smokers [34]. In a retrospective study, an observational cohort study of 112 in-patient adults, diagnosed with COVID-19, between March 12 and April 16, 2020, in Los Angeles, smoking history along with obesity and elevated inflammatory markers was associated with an increased need for invasive mechanical ventilation in patients with COVID-19 [35].…”
Section: Resultsmentioning
confidence: 99%
“…A study in Iran showed that among 193 confirmed COVID-19 patients, more than half of cigarette smokers and 40% of waterpipe smokers reported their COVID-19 symptoms as severe compared to 22% of never-smokers [34]. In a retrospective study, an observational cohort study of 112 in-patient adults, diagnosed with COVID-19, between March 12 and April 16, 2020, in Los Angeles, smoking history along with obesity and elevated inflammatory markers was associated with an increased need for invasive mechanical ventilation in patients with COVID-19 [35].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other tobacco products that are typically used solitarily, hookah smoking usually occurs in groups, where smokers often pass the same hose to smoke with friends 26 . It is possible that because of the sharing culture of hookah smoking, smokers are more concerned regarding the risk of infection, 27 therefore, were more likely to get tested for COVID‐19. Although it is hard to parse out the pipe from a hookah in NHIS (since they were asked within the same item), this finding has important public health implications while awaiting future studies to explore vaccine hesitancy and acceptance based on the specific type of tobacco product as well as the pattern of use (e.g., intensity and frequency).…”
Section: Discussionmentioning
confidence: 99%